Solid urban waste - a management model in small and mid-sized cities - Luiz Martins, Benedito; José Esguicero, Fabio; Wagner de Souza Manfrinato, Jair (Revista Gestão da Produção Operações e Sistemas, 2009)
For most Brazilian cities, good solid waste management is a challenge. The public administrator has difficulty in organizing the collection, transport, treatment and the final disposal of solid wastes encompassing social, environmental, sanitary and legal aspects. An integrated solid waste management plan was organized by the municipality of Lençóis Paulista, a city with 62,894 inhabitants in the state of São Paulo, and the Paulista State University (UNESP), Botucatu Campus. The plan detected the precarious conditions of the solid waste management system and society´s omission regarding the physical handicapped and other poor people who sorted the recycling materials from the trash. The plan revitalized and restructured the Recycling and Composting Factory and conventional collections and introduced a selective collection system. The results emerged with the formation of the recycling cooperative formed by poor people, in partnership with the association of physical handicapped people, generating social inclusion, increasing recycling and the useful life of the landfill. Key words: Recycling; Social inclusion; Management plan.